MIMO Radar Transmit Beampattern Matching Design - Xiaojun Zhang; Zishu He; Rayman-Bacchus, Lez; Jihong Yan (IEEE transactions on signal processing, 2015)
In this paper, a novel transmit beampattern matching design method is proposed for a multiple-input multiple-output (MIMO) radar system. Whereas previous approaches first solve the correlation matrix R and then use R to design the transmit signal S, the proposed one-step method obtains the transmit signal S directly through solving the waveform matrix P. Since MIMO radar transmit beampattern matching design is an inverse problem of the transmit beampattern, in this paper, we first discuss some important properties of the transmit beampattern and standardize the beampattern matching design problem. We then theoretically explain the value of the signal waveform matrix P, followed by an unconstrained optimization problem to solve P. Numerical examples demonstrate the advantages of the proposed one-step method for the MIMO radar transmit beampattern matching design problem, including uniform and non-uniform linear arrays.